Internal and External Factors in Developing Farmer Businesses in Pinrang Regency, South Sulawesi Province, Indonesia (Case Study) - St. Rohani; Siti Nurlaelah; Sitti Nurani Sirajuddin; Mukhlis Mukhlis; Ilham Syarif (Postgraduate, University of Mataram, 2024)
This study aimed to identify external and internal factors in community businesses in Alitta Village. The study was conducted in Alitta Village, Mattiro Bulu District, Pinrang Regency in May 2024. The analysis used in this study was a SWOT analysis. The results of the study showed that internal factors are management, finance, human resources, facilities and infrastructure, and legal umbrella while external factors are technology, business partners, government, village potential, community participation and competitors. BUMDes development is carried out with a focus on three main aspects: improving the village economy, developing existing potential, and managing this potential to meet the needs of the local community. Meanwhile, the lack of human resources for BUMDes management, the difficulty of maintaining the agricultural machinery owned and the supply of raw material inputs that are not smooth. Efforts to overcome obstacles through strategy development can be an option to be implemented, namely Increasing product availability, recruiting new members to run each business division and opening independent outlets. Significant impact because gasoline is an important commodity needed by rural communities. Most farmers who rely heavily on water pumps to irrigate their agricultural land. Gasoline supply shortages cause delays and disruptions in the operation of such equipment, hampering agricultural productivity.